South African Heart Association newsletter - Autumn 2013 - Snyders, Adriaan (SA Heart Journal, 2017)
SA Heart Journal will now also be available and distributed in electronic format with only a limited number of printed copies in order to contain costs. Please read this as carefully as you have read the printed version and feel free to comment on our ideas. We would like to know if our two weekly e-Bulletin is of any value and what other information you would like to see included in either the newsletter and/or the e-Bulletin. Our new website will have a discussion forum on which different topics will be discussed from time to time. Please feel free to browse and experiment and do not hesitate to give us your much valued feedback.